Sebuah Kasus : Post Tonsilektomi Dengan Komplikasi Syok Hipovolemik - Siti Sapura; Fahrizal Fahrizal (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Tonsillitis is inflammation of the palatine tonsils. Infection of the tonsils occurs if antigens, whether inhaled or ingested, easily enter the tonsils and the body resists and a focus of infection forms. Initially, the infection is acute, generally caused by viruses that grow on the mucous membrane, then followed by bacterial infection. As a result of chronic inflammation, the size of the tonsils will increase due to parenchymal hyperplasia or fibrinoid degeneration with tonsillar crypt obstruction. The definitive treatment for chronic tonsillitis is surgical removal of the tonsils or tonsillectomy where one of the complications is bleeding which triggers hypovolemic shock. This case report presents a 19 year old man who complained of pain in swallowing and a feeling of lump in the throat and based on the history, physical examination and supporting examinations that had been carried out, the patient was diagnosed with tonsillitis and planned to undergo a tonsillectomy. After the procedure, the patient experienced hypovolemic shock due to bleeding and died